CORRELATION OF BASED SOIL CARRYING CAPACITY RESULTS OF CONE PENETRATION TEST, DYNAMIC CONE PENETROMETER (DCP), PLATE BEARING TEST, AND HAND PENETROMETER - Kameistu, Ponsianus; Priadi, Eka; Widodo, Slamet (Fakultas Teknik Universitas Tanjungpura, 2023)
Several testing methods can be carried out in testing the bearing capacity of the soil, such as soil test testing, hand penetrometer, dynamic cone penetrometer, plate bearing test, and others. In addition to direct testing in the field, testing can also be carried out in the laboratory. The purpose of this study is to determine how much the correlation results of the 4 (four) test methods are to provide efficient results in data collection in the field. The location of research was carried out in Sekadau Regency, Sekadau Hilir District. The Sports Stadium Complex Development Plan has carried out as many as 20 (twenty) points for each test. Each test was carried out closely and reviewed at a depth of one meter, with soil characteristics at The test location being sandy soil with fine grain. The correlation test was carried out with 4 (four) test methods using the regression line method. This study shows a solid correlation between CBR Dynamic Cone and Hand Penetrometer (r = 0.893). The strong correlation between Hand Penetrometer and the qc Soil test (r = 0.669). Good modulus subgrade (Plate Bearing Test) correlation with CBR Dynamic Cone Penetrometer (r = 0.417). Very weak correlation of Soil test qc with subgrade modulus (Plate Bearing Test (r = 0.226).